Transparency in the Netflix Series Baitu Tahir Subtitles and Its Implications for Dynamic Equivalence - Adawiyah, Alfina Robi'ah; Ma'nawi, Arief; Sajarwa, Sajarwa; Syafran, Ahmad; Octavianti, Dinda Sekar; Ginola, David (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article presented the subtitles transparency from the Netflix series Baitu Tahir. Additionally, the implications of transparency were illustrated on dynamic equivalence. In this article, the Arabic and Indonesian subtitles were analyzed from the first episode, focusing on 569 data points using a descriptive qualitative comparative method. In this study, Venuti's theory identified translation techniques, while Nida's theory examined dynamic equivalence. The analysis revealed that foreignization (literal translation, transposition, and borrowing) and domestication (omission, transposition, addition, and adaptation) are both employed, with 68 instances of foreignization and 501 of domestication. The findings indicated that domestication is used more frequently to create a natural effect in Indonesian, the target language (TL). The balance of dynamic equivalence and transparency was crucial for ensuring subtitle accessibility while preserving cultural nuances. The study underscores the importance of strategic translation choices in subtitling, ultimately contributing to a better understanding of how foreign and domestic elements influence viewers' comprehension and the overall quality of translated content on global platforms like Netflix.